"There Ain't No Such Thing as a Free Lunch": Consumers' Reactions to Pseudo-Free Offers. (December 2018) - Dallas, Steven K.; Morwitz, Vicki G.
The authors examine how consumers respond to pseudo-free offers—offers that are presented to consumers as free but that require consumers to make a nonmonetary payment (such as completing a survey or providing personal information) in order to receive the "free" good or service. Across six studies, the authors find that consumers are generally just as likely to accept pseudo-free offers (with nonmonetary costs) as comparable truly free offers (with no costs), as long as the costs of the pseudo-free offers are below some threshold. Additionally, they find that consumers are significantly more likely to accept pseudo-free offers (with nonmonetary costs) than comparable nonfree offers (with monetary costs). The authors provide evidence that consumers respond to pseudo-free offers in this way because, in general, consumers generate neutral or positive attributions for why firms make these offers, and these attributions, in turn, lead consumers to perceive the pseudo-free offers as fair. However, when contextual influences, characteristics of the pseudo-free offer, or individual dispositions increase the likelihood of negative attributions, consumers' preference for pseudo-free offers is attenuated.